Development of a distributed modeling framework to estimate thermal comfort along 2020 Tokyo Olympic marathon course - Hirabayashi, S.; Abe, T.; Imamura, F.; Morioka, C. (Atmosphere, 2018)
Heat stress is an issue for marathon races in the summer, such as the one planned for the 2020 Tokyo Summer Olympic Games. The Tokyo Metropolitan Government is planning to grow existing street trees` canopies to enlarge their shade to reduce air temperature and solar radiation. To formulate a baseline to assess the effect of street trees and buildings on human thermal comfort, Distributed-COMfort FormulA (D-COMFA), a prototype of a distributed computer model using a geographic information system (GIS) was developed. D-COMFA calculates the energy budget of a human body on a 1 m cell basis, using readily available datasets such as weather measurements and polygon data for street structures. D-COMFA was applied to a street segment along the marathon course in Tokyo on an hourly-basis on 9 August 2016, the hottest day in Tokyo in 2016. Our case study showed that the energy budget was positively related to the sky view factor, air temperature, and solar radiation. The energy budget was reduced on average by 26-62% in the shade throughout the day.